Making Kin with Multispecies’ Flourishing in the Anthropocene: A Multiperspectival Narrative Into Environmental and Sustainability Education - Tran, Thi Thuy Hang; Bui, Tram-Anh; Kenton, Dianne J.; Rajasekharan, Sreedevi; Lu, Olivia; Khan, Steven (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
The development of Environmental and Sustainability Education (ESE) in pre-service teacher education in Canada has shown slow but steady progress over the past 40 years. A detailed history of how individuals and groups have influenced its praxis does not yet exist (Elliott & Inwood, 2019, p. 37). This paper attends to the experiences of six teacher educators/graduate students who have been composing their lives in different landscapes in relation to ESE. We employ collaborative autoethnography as our research methodology. Together, we are involved in the process of telling, retelling, and reliving our stories of who we are in relation to ESE. We also pay deep attention to the resonances echoed across our experiences and curate our forward-looking thoughts for/with the future of ESE. We hope to expand current ESE with a more holistic and sustainable approach, which includes integrating place-based wisdom with environmental education; collaborating with material presences not as resources but as partners for multispecies’ flourishing; and sustaining the intergenerational reverberations of familial and cultural practices and quantitative literacy.